The Social Construction of Early Marriage in Tanjungpinang City: Intersections of State Law, Religious Norms, and Community Values - Desmayeti Arfa; Endri Bagus Prastiyo; Alfi Husni; Rianto Rianto; Desi Meliasari (Journal of Social and Policy Issues, 2025)
This study aims to analyze the social construction of early marriage in Dompak Urban Village, Bukit Bestari Sub-District, Tanjungpinang City, by examining how community perceptions, norms, and interactions shape attitudes toward early marriage practices. Employing a descriptive qualitative approach, the research collected data through observation, in-depth interviews, and documentation involving community members, religious figures, and local stakeholders. Data were analyzed using the social construction theory to explore how shared meanings and collective agreements regarding early marriage are formed and maintained within the community. The findings reveal that early marriage in Dompak Village is socially constructed through continuous social interaction, where customary norms, religious interpretations of Islamic law, and collective values play a dominant role. The community perceives early marriage as a legitimate and even beneficial practice, often viewed as a destined match that serves both individual and collective interests. This social construction persists despite existing national marriage regulations that set minimum age requirements, indicating a tension between state law and local cultural-religious norms. The study concludes that early marriage in Dompak Village is sustained by a socially constructed reality rooted in shared beliefs and religious legitimacy rather than legal compliance. Therefore, stronger governmental engagement is required through consistent legal socialization, stricter regulation of marriage dispensations, and educational interventions emphasizing the importance of continued education and family well-being to prevent the normalization of early marriage practices.